Net Assets Recognition and Valuation in Transformation of Czech Companies - Pospíšil, Jiří, 1988- (2018)
The aim of this thesis is to examine the concept of accounting and financial reporting for business combinations. An emphasis is put to legal mergers, splits,spin-offs and other transactions referred to as “business transformations” under the Czech regulation. In this thesis I analyse the accounting solutions prescribed for this type of transactions by the national legal regulation and compare these solutions to the generally accepted accounting methods for business combinations. Moreover I compare these solutions to the methods applied in the neighbouringcountries and regulation of IAS/IFRS. This thesis contributes to the available literature on accounting for business combinations in the Czech Republic. A criticalanalysis of applicable accounting regulation is included together with the recommendation for modification of the current regulation to make it more conforming to the factual nature of the analyses transactions and at the same time,more compatible with the regulation of IAS/IFRS and the generally accepted principles for accounting for business combinations as well.